Preliminary report: An application of the Good Behavior Game in the developing nation of Belize. (August 2014) - Nolan, Julene D.; Filter, Kevin J.; Houlihan, Daniel
Educating children on a global level is a dynamic process where policy, procedure and guideline changes can leave teachers searching for new programs to resolve new challenges. This brief report shows a successful application of the Good Behavior Game in a school in the country of Belize following a significant change in policy regarding acceptable practices in addressing school-based behavioral challenges.